2006
DOI: 10.1523/jneurosci.3175-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Sleep Spindle Density after Learning or after Retrieval in Rats

Abstract: Non-rapid eye movement sleep has been strongly implicated in consolidation of both declarative and procedural memory in humans. Elevated sleep-spindle density in slow-wave sleep after learning has been shown recently in humans. It has been proposed that sleep spindles, 12-15 Hz oscillations superimposed on slow waves (Ͻ1 Hz), in concert with high-frequency hippocampal sharp waves/ripples, promote neural plasticity underlying remote memory formation. The present study reports the first indication of learning-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
199
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(220 citation statements)
references
References 52 publications
16
199
1
Order By: Relevance
“…Increasingly, sleep spindles, one of the most prominent features of NREM, have been implicated in these plastic processes (5,7,8,17,29). It has been postulated that spindles facilitate synaptic plasticity in cortical cells via calcium-dependent mechanisms (11), and it has been shown that cortical stimulation at the spindle frequency increases synaptic plasticity (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasingly, sleep spindles, one of the most prominent features of NREM, have been implicated in these plastic processes (5,7,8,17,29). It has been postulated that spindles facilitate synaptic plasticity in cortical cells via calcium-dependent mechanisms (11), and it has been shown that cortical stimulation at the spindle frequency increases synaptic plasticity (30).…”
Section: Resultsmentioning
confidence: 99%
“…This dissociation could provide a window for uninterrupted replay of recently instantiated memories and thus support sleep-dependent memory consolidation. There is now a large body of evidence linking sleep spindles to learning and memory in both humans and animals (5)(6)(7). For example, increases in spindle density have been correlated with learning a declarative memory task (5), with retention of verbal memories (6), and with relevant recall of a remote memory (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these hippocampal events include replayed place cell sequential offline firing, and that their activity coincides with cortical UP states, it is thought that they may play an important role in the coordination of corticohippocampal activity necessary for memory consolidation[21]. Additionally, UP states appear to coordinate SWR-spindle events, which occur at an increased incidence after learning, further supporting a role of this rhythm in memory consolidation[64,65]. …”
Section: Neuronal Substrates Of Slow Oscillationsmentioning
confidence: 99%
“…This imposes an inhibitory rhythmic synaptic drive onto thalamocortical cells, which ultimately results in entrainment of the cortex to that rhythm[67]. Work by Sara’s lab has shown that spindle density rises in the cortex as a function of learning, suggesting that this rhythm might be important for off-line memory processing[68]. Interestingly, while slow oscillations and delta oscillations are low-frequency rhythms that are classically thought to promote synaptic depression, a number of experiments support a role for spindle oscillations in the induction of cortical long-term potentiation[69].…”
Section: Neuronal Substrates Of Slow Oscillationsmentioning
confidence: 99%